Technology Transfer in Introduction of Learning English Using Kahoot Application in Elementary School - Puspitasari, Viera Aulia; Susiati, S (Universitas Muhammadiyah Surakarta, 2023)
This research aims to find out the introduction of learning English by implementing Kahoot as media in elementary school and exploring students' perception about using Kahoot in learning English. The method of this research is descriptive qualitative research. The participants were 32 students exactly in 5th grade academic year 2022/2023. The students consist of 15 male students and 17 female students. The age range is 10 – 12 years old. Data collected through interviews of 6 students. This, 6 students taken from the 3 people with the highest scores and the 3 people with the lowest scores. Then all the data were analysed qualitatively. This research found that One great method is to educate English by utilizing technology such as Kahoot that 1) makes students enjoy the teaching and learning process, 2) aids students in understanding and learning English, 3) boots students' motivation, and 4) build students' positive competition. All the participants giving a positive review after learning English using Kahoot in the classroom. Kahoot could be effortlessly combined with alternative teaching approaches in order to give meaningful language learning experience.